2019
DOI: 10.1186/s12967-019-1805-7
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin regulates bone mass in AIS osteopenia via RANKL/OPG and IL6 pathway

Abstract: Background Osteopenia have been well documented in adolescent idiopathic scoliosis (AIS). Adiponectin has been shown to be inversely proportional to body mass index and to affect bone metabolism. However, the circulating levels of adiponectin and the relationship between adiponectin and low bone mass in AIS remain unclear. Methods A total of 563 AIS and 281 age-matched controls were recruited for this study. Anthropometry and bone mass were measured in all participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…Our results showed that adiponectin deficiency induced a low bone mass by increased RANKL/OPG ratio that is opposite of a recent report (39). Zhang et al investigated the relationship between adiponectin and low bone mass in in patients with adolescent idiopathic scoliosis (AIS).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that adiponectin deficiency induced a low bone mass by increased RANKL/OPG ratio that is opposite of a recent report (39). Zhang et al investigated the relationship between adiponectin and low bone mass in in patients with adolescent idiopathic scoliosis (AIS).…”
Section: Discussioncontrasting
confidence: 99%
“…Dramatically reduced production of leptin, a potent inhibitor of bone formation (44,45), contributes, at least in part, to the high bone mass phenotype of the mutant mice. Adiponectin, an adipocyte-derived cytokine, exerts an inhibitory effect on bone metabolism (46,47). Because kindlin-2 loss dramatically reduced the blood levels of adiponectin ( Figure 4M), it is possible that the reduction in adiponectin also contributes to the high bone mass phenotype of the mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, we verified that downregulation of kindlin-2 reduces the level of leptin and adiponectin which are two effective osteogenesis inhibitors. Therefore, the reduction of leptin and adiponectin may contribute to increased osteogenic differentiation (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%